Preparation method of geopolymer concrete of mixture of thermally activated muck, cement and calcium hydroxide and prefabricated bay window
By thermally activated slag, cement and calcium hydroxide mixture geopolymer concrete preparation method, and using construction slag as the main raw material, the problems of high energy consumption and environmental pollution in the traditional concrete manufacturing process are solved, and the industrial waste resources are realized. The secondary use and recycling of resources reduce construction costs and improve the mechanical properties of concrete.
Patent Information
- Application Number
- CN202411613779.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-13
AI Technical Summary
Traditional concrete manufacturing process relies on a large amount of natural resources, resulting in high energy consumption and environmental pollution, and a large amount of greenhouse gases are generated during cement production, seriously affecting the global greenhouse effect.
By thermally activate the preparation method of the slag, cement and calcium hydroxide mixture of geopolymer concrete, building slag is used as the main raw material to reduce dependence on traditional raw materials, reduce energy consumption and emissions, and stimulate the activity of slag through high-temperature calcination. A geopolymer gel with high strength and bondability is formed.
It significantly reduces the dependence on traditional concrete raw materials, reduces energy consumption and greenhouse gas emissions during raw material mining, realizes the rational secondary use of industrial waste resources, promotes the recycling of resources, saves construction costs, and increases The mechanical properties of concrete.
Smart Images

Figure CN119461970A_ABST
Abstract
Description
[Technical field] The invention relates to the technical field of building materials, and in particular to a method for preparing geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide, and a prefabricated bay window using the geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide prepared by the preparation method. [Background technology] The traditional concrete manufacturing process not only relies on a large amount of natural resources, such as sand and stone aggregates, but also its energy consumption and environmental pollution problems in the production process have been criticized. Especially in the cement production process, data show that for every ton of Portland cement produced, about 1.5 tons of limestone and a large amount of coal and electricity are required, and a large amount of carbon dioxide is also emitted. Studies have shown that greenhouse gas emissions generated by cement production account for a considerable proportion of total human emissions, exacerbating the global greenhouse effect. In addition, the raw materials of traditional concrete mainly come from natural resources, such as sand and stone aggregates. The mining of these resources not only consumes a lot of energy, but also may lead to resource depletion and ecological damage. With the increase in the use of concrete, the demand for raw materials such as sand and stone has also continued to rise. Some areas have already experienced problems of sand and stone resource shortages and ecological damage.
[0003] In addition, with the acceleration of urbanization, the amount of waste generated by construction projects is increasing, which has brought a heavy burden to the environment. [Summary of the invention] The object of the present invention is to provide a method for preparing geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide, which can utilize waste such as construction slag as raw materials, reduce dependence on traditional raw materials, reduce energy consumption and emissions in the production process, and reduce environmental pollution, aiming to solve the above-mentioned problems existing in concrete manufacturing in the prior art.
[0005] The present invention is achieved by the following technical solutions: The method for preparing geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide comprises the following steps: a. Raw material preparation: obtain slag from the project excavation; b. Raw material pretreatment: drying and sieving the slag in step a to obtain dry slag powder and slag particles of suitable particle size; c. Activation: adding ordinary cement and an alkali activator to the slag powder and the slag particles in step b, and calcining them at high temperature to obtain an activated mixture; d. Preparation of pure slurry: mixing the activated mixture in step c with an alkaline solution and water to prepare a pure slurry material; e. Concrete preparation: The clean slurry material in step d is mixed with coarse aggregate, fine aggregate and admixture to obtain geopolymer concrete slurry of a mixture of heat-activated slag, cement and calcium hydroxide.
[0006] The working principle of the present invention is mainly based on the formation mechanism of geopolymer concrete. Geopolymer concrete is a new type of concrete formed by stimulating the activity of industrial waste or natural minerals through alkaline activators, so that they react chemically with materials such as cement. In the present invention, the slag obtained from the excavation of the project is first pretreated to obtain dry slag powder and slag particles of suitable particle size. Then, ordinary cement, alkali activator, slag powder and slag particles are added and mixed, and calcined under high temperature conditions to stimulate the activity of the slag. Under the action of the alkaline activator, the aluminosilicate minerals in the slag undergo dissolution and polycondensation reactions to generate a geopolymer gel with a three-dimensional network structure. This gel has high strength and adhesion, and can significantly improve the performance of concrete. Finally, the activated mixture is mixed with an alkaline solution and water in a certain proportion to prepare a slurry material, and mixed with coarse aggregate, fine aggregate and admixtures to obtain a geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide.
[0007] The present invention uses the slag obtained from the excavation of the project as the main raw material, significantly reducing the dependence on traditional concrete raw materials (such as sand and stone aggregates). This not only reduces the energy consumption in the process of raw material mining, but also reduces the emission of related greenhouse gases (such as carbon dioxide), thereby effectively alleviating the global greenhouse effect.
[0008] By stimulating the activity of slag through high-temperature calcination, the rational secondary use of industrial waste resources (i.e. slag) is achieved, and the recycling of resources is promoted. This not only helps to alleviate the problem of resource shortage, but also reduces the over-exploitation of natural resources, which is in line with the concept of sustainable development.
[0009] In addition, compared with traditional cement production, this method produces less waste during the production process, and the environmental performance can be further optimized by adjusting the formula and process parameters. In addition, since the mining of raw materials such as sand and gravel is reduced, the damage to the ecological environment is also reduced accordingly.
[0010] Through the preparation process proposed in the present invention, the heat-activated slag, cement and calcium hydroxide mixture geopolymer concrete obtained in the present invention not only has the mechanical properties of traditional concrete, but also saves construction costs, greatly reduces the transportation and treatment costs of construction slag, and brings significant economic benefits to the enterprise.
[0011] Preferably, in the present invention, the drying temperature in step b is 100-110° C., the drying time is 24 hours, and the particle size of the slag particles is less than or equal to 1.5 mm and greater than or equal to 4.75 mm.
[0012] Drying is performed to ensure that the slag is fully dried and to remove free water and part of the bound water, thereby improving the quality and stability of subsequent concrete preparation. At the same time, this drying condition is also standardized, which is convenient for accurate control in actual operation. The selection of the particle size range of slag particles helps to improve the density and working performance of concrete. Specifically, small particles can fill the gaps between large particles and improve the density of concrete; while large particles can provide a better aggregate structure and enhance the mechanical properties of concrete.
[0013] Preferably, in the present invention, the high temperature condition in step c is 700-750° C., the calcination time is 2 hours, and the particle size of the slag particles is less than or equal to 1.5 mm.
[0014] High-temperature calcination can effectively stimulate the activity of slag, causing the aluminosilicate minerals therein to undergo phase change and activation, thereby improving the reactivity with materials such as cement. This helps to form a more stable and better-performing geopolymer gel in subsequent steps. The use of slag particles with a particle size less than or equal to 1.5 mm in step c helps to improve the calcination effect and the performance of subsequent concrete. This is because small-sized slag particles have a larger specific surface area and can more fully contact and react with the alkali activator, thereby increasing the amount and quality of geopolymer gel produced. In addition, high-temperature calcination can be carried out in a muffle furnace to ensure the uniformity and stability of the calcination process. The muffle furnace has good temperature control and regulation capabilities and can provide a constant calcination environment, thereby ensuring uniform activation of slag particles and the generation of high-quality geopolymer gel.
[0015] Preferably, in the present invention, the alkaline solution in step d is a sodium carbonate solution prepared by dissolving sodium carbonate and water in advance, and the amount added is preferably 7% to 9% by weight of the total amount of the liquid activator and the solid raw materials.
[0016] Sodium carbonate solution can promote the dissolution and condensation of aluminosilicate minerals in slag to form geopolymer gel, thereby improving the strength and durability of concrete. It helps to ensure the adequacy and moderation of the alkali activation process, avoid the degradation of concrete performance caused by excessive or insufficient alkali, maximize the activity of slag, and improve the generation efficiency and quality of geopolymer gel.
[0017] Preferably, in the present invention, the water-to-solid ratio in the mixing process of step e is preferably 25% to 32%.
[0018] When the water-solid ratio is between 25% and 32%, the moisture in the concrete can fully meet the needs of cement hydration reaction without causing excessive pores, which enables the concrete to achieve the highest strength and durability while maintaining good working performance.
[0019] Preferably, in the present invention, the weight mix ratio of the heat-activated slag, cement and calcium hydroxide mixture geopolymer concrete in step e is activated mixture: sodium carbonate: fine aggregate: coarse aggregate: water = 1: 0.2~0.4: 1.5~1.7: 1.2~1.4: 0.1~0.2, the coarse aggregate is preferably the slag particles with a particle size greater than or equal to 4.75 mm, and the fine aggregate is preferably medium sand with a particle size of 1.0 mm~2.0 mm.
[0020] By specifying a specific mix ratio, it is possible to ensure that the heat-activated slag, cement and calcium hydroxide mixture geopolymer concrete has consistent performance each time it is prepared, thereby improving the stability and reliability of the concrete. The aggregate structure of the concrete can be optimized by using slag particles with a particle size greater than or equal to 4.75 mm as coarse aggregate and medium sand with a particle size of 1.0 mm to 2.0 mm as fine aggregate. The coarse aggregate provides the main skeleton support, while the fine aggregate fills the gaps between the coarse aggregates, together forming a compact internal structure of the concrete, thereby enhancing the structural strength of the concrete.
[0021] Preferably, in the present invention, the alkaline activator in step c is calcium hydroxide.
[0022] During the high-temperature calcination process in step c, calcium hydroxide, as a strong alkaline activator, can promote the thermochemical transformation of active ingredients such as silicates in the slag. This transformation includes the decomposition of minerals, the generation of active silica-alumina oxides, etc., thereby significantly improving the reactivity of the slag. Under the combined action of high temperature and calcium hydroxide, the formation of geopolymer gel can be promoted. Specifically, during high-temperature calcination, calcium hydroxide reacts with active silica-alumina oxides in the slag to generate precursors of geopolymer gel. These precursors will further react in the subsequent concrete preparation process. For example, when mixed with an alkaline solution (sodium carbonate solution) in step d, they can participate in the reaction more quickly and completely, thereby generating more geopolymer gel, which helps to improve the strength and durability of the net slurry material.
[0023] In addition, the high-temperature calcination treatment in step c not only stimulates the activity of the slag, but also changes its microstructure, such as reducing porosity and making the particle surface rougher. These changes are conducive to making it easier for the alkaline solution (sodium carbonate solution) to penetrate into the interior of the activated mixture when preparing the slurry in step d, fully contact and react with the active ingredients therein, thereby generating a more uniform and dense geopolymer gel network. It should be added that after the activated mixture generated in step c is mixed with the alkaline solution (sodium carbonate solution) in step d, its highly active ingredients can quickly react with the water and alkali metal ions in the solution to generate a large amount of hydration products. These hydration products fill the pores of the slurry material, further improving its density and strength.
[0024] Preferably, in the present invention, the admixture includes S105 grade ground granulated blast furnace slag and F class fly ash, the particle size of the F class fly ash is less than 45μm, the specific surface area is 400m² / kg~450m² / kg, and the dosage range is 12~15%; the particle size of the S105 grade ground granulated blast furnace slag is less than 45μm, the specific surface area is 500m² / kg~520m² / kg, and the dosage range is 10~13%.
[0025] The fineness and high specific surface area of blast furnace slag help it better combine with other ingredients in concrete to form a stronger structure. It should be noted that particle size and specific surface area are key factors affecting the effect of admixtures. Smaller particle size and larger specific surface area mean that more particle surface can react with other ingredients, thereby improving the efficiency and degree of the reaction.
[0026] The active ingredients in Class F fly ash and blast furnace slag (such as silicon dioxide, aluminum oxide, etc.) can react with calcium hydroxide and other ingredients in concrete in an alkaline environment to generate hydration products with cementitious properties (such as calcium silicate hydrate, calcium aluminate hydrate, etc.). These hydration products can fill the voids in the concrete and form a strong network structure, thereby improving the performance of the concrete.
[0027] The present invention also proposes a prefabricated bay window, comprising a bay window body, one side of which is evenly provided with CFRP connecting ribs fixed to the building structure, and the material of the bay window body is the heat-activated slag, cement and calcium hydroxide mixture geopolymer concrete prepared by the above preparation method.
[0028] Compared with the prior art, the present invention has the following advantages: 1. The method for preparing geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide proposed in the present invention significantly reduces the dependence on traditional concrete raw materials (such as cement, sand, stone aggregates), reduces energy consumption and greenhouse gas emissions in the process of raw material mining, and thus effectively alleviates the global greenhouse effect. This advantage is mainly achieved by using slag obtained from project earthwork excavation as the main raw material, which not only solves the problem of handling construction slag, but also reduces the exploitation of natural resources.
[0029] 2. The present invention stimulates the activity of slag through high-temperature calcination treatment, realizes the reasonable secondary use of industrial waste resources (i.e. slag), and promotes the recycling of resources. This not only helps to alleviate the problem of resource shortage, but also reduces the over-exploitation of natural resources, which is in line with the concept of sustainable development.
[0030] 3. The heat-activated slag, cement and calcium hydroxide mixture geopolymer concrete prepared by the preparation process proposed by the present invention not only has the mechanical properties of traditional concrete, but also saves construction costs, greatly reduces the transportation and treatment costs of construction slag, and brings significant economic benefits to enterprises. This advantage is mainly achieved by using slag, which was originally a waste, as raw material and optimizing the preparation process.
[0031] 4. The present invention can prepare heat-activated slag, cement and calcium hydroxide mixture geopolymer concrete with excellent performance through the preferred process parameters, such as drying temperature, drying time, slag particle size, high temperature calcination conditions, selection and addition amount of alkaline solution, water-solid ratio and specific mix ratio, etc. These preferred process parameters are helpful to improve the strength, durability and workability of concrete.
[0032] 5. The present invention also proposes to apply the prepared geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide to the manufacture of prefabricated bay windows, which further expands the application field of geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide and improves its market value. The structural stability and safety of the prefabricated bay windows are enhanced by fixing the CFRP connecting bars to the building structure.
Brief Description of the Drawings
[0034] Figure 1 Schematic diagram of the preparation process of Examples 1-3 of the present invention; Figure 2 This is a schematic diagram of the structure of Embodiment 4 of the present invention; Figure 3 This is a mise analysis diagram of the prefabricated bay window concrete of Example 4 of the present invention; Figure 4 This is a mise analysis diagram of CFRP steel bars for prefabricated bay windows in Example 4 of the present invention. [Specific implementation method] In order to make the technical problems, technical solutions and beneficial effects solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0036] Example 1 This embodiment provides a geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide, wherein the weight mix ratio is: activated mixture: sodium carbonate: fine aggregate: coarse aggregate: water = 1:0.3:1.5:1.2:0.1.
[0037] The activated mixture includes slag particles with a particle size less than or equal to 1.5 mm, slag powder, ordinary cement, and calcium hydroxide; the fine aggregate is medium sand with a particle size of 1.8 mm, and the coarse aggregate is slag particles with a particle size greater than or equal to 4.75 mm.
[0038] The preparation method comprises the following steps: a. Raw material preparation: obtain slag from the project excavation; b. Raw material pretreatment: drying and sieving the slag in step a in an oven at a drying temperature of 100-110° C. for 24 hours to obtain dry slag powder and slag particles of suitable particle size, wherein the slag particles include two specifications of particle size less than or equal to 1.5 mm and greater than or equal to 4.75 mm; c. Activation: adding ordinary cement, calcium hydroxide, the slag powder in step b and slag particles with a particle size of less than or equal to 1.5 mm, and mixing, and placing in a muffle furnace and calcining at 700-750° C. for 2 hours to obtain an activated mixture; d. Preparation of pure slurry: mixing the activated mixture in step c with sodium carbonate solution and water to prepare a pure slurry material; e. Concrete preparation: The slurry material in step d is mixed with coarse aggregate (slag particles with a particle size greater than or equal to 4.75 mm), fine aggregate (medium sand with a particle size of 1.8 mm) and admixture (12% of Class F fly ash and 13% of S105 grade ground granulated blast furnace slag) to obtain a geopolymer concrete slurry of a mixture of heat-activated slag, cement and calcium hydroxide.
[0039] After the heat-activated slag, cement and calcium hydroxide mixture geopolymer concrete is prepared, the heat-activated slag, cement and calcium hydroxide mixture geopolymer concrete slurry is poured into a mold (150mm×150mm×150mm cubic mold, a total of 12 molds are cast), and a vibration table and manual plugging are used to make it dense, and then it is smoothed and covered with plastic film for maintenance for 28 days.
[0040] Example 2 This embodiment provides a geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide, wherein the weight mix ratio is: activated mixture: sodium carbonate: fine aggregate: coarse aggregate: water = 1:0.2:1.6:1.3:0.2.
[0041] The activated mixture includes slag particles with a particle size less than or equal to 1.5 mm, slag powder, ordinary cement, and calcium hydroxide; the fine aggregate is medium sand with a particle size of 1.8 mm, and the coarse aggregate is slag particles with a particle size greater than or equal to 4.75 mm.
[0042] The preparation method comprises the following steps: a. Raw material preparation: obtain slag from the project excavation; b. Raw material pretreatment: drying and sieving the slag in step a in an oven at a drying temperature of 100-110° C. for 24 hours to obtain dry slag powder and slag particles of suitable particle size, wherein the slag particles include two specifications of particle size less than or equal to 1.5 mm and greater than or equal to 4.75 mm; c. Activation: adding ordinary cement, calcium hydroxide, the slag powder in step b and slag particles with a particle size of less than or equal to 1.5 mm, and mixing, and placing in a muffle furnace and calcining at 700-750° C. for 2 hours to obtain an activated mixture; d. Preparation of pure slurry: mixing the activated mixture in step c with sodium carbonate solution and water to prepare a pure slurry material; e. Concrete preparation: The slurry material in step d is mixed with coarse aggregate (slag particles with a particle size greater than or equal to 4.75 mm), fine aggregate (medium sand with a particle size of 1.8 mm) and admixture (15% of Class F fly ash and 12% of S105 grade ground granulated blast furnace slag) to obtain a geopolymer concrete slurry of a mixture of heat-activated slag, cement and calcium hydroxide.
[0043] After the heat-activated slag, cement and calcium hydroxide mixture geopolymer concrete is prepared, the heat-activated slag, cement and calcium hydroxide mixture geopolymer concrete slurry is poured into a mold (150mm×150mm×150mm cubic mold, a total of 12 molds are cast), and a vibration table and manual plugging are used to make it dense, and then it is smoothed and covered with plastic film for maintenance for 28 days.
[0044] Example 3 This embodiment provides a geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide, wherein the weight mix ratio is: activated mixture: sodium carbonate: fine aggregate: coarse aggregate: water = 1:0.4:1.6:1.3:0.2.
[0045] The activated mixture includes slag particles with a particle size less than or equal to 1.5 mm, slag powder, ordinary cement, and calcium hydroxide; the fine aggregate is medium sand with a particle size of 1.8 mm, and the coarse aggregate is slag particles with a particle size greater than or equal to 4.75 mm.
[0046] The preparation method comprises the following steps: a. Raw material preparation: obtain slag from the project excavation; b. Raw material pretreatment: drying and sieving the slag in step a in an oven at a drying temperature of 100-110° C. for 24 hours to obtain dry slag powder and slag particles of suitable particle size, wherein the slag particles include two specifications of particle size less than or equal to 1.5 mm and greater than or equal to 4.75 mm; c. Activation: adding ordinary cement, calcium hydroxide, the slag powder in step b and slag particles with a particle size of less than or equal to 1.5 mm, and mixing, and placing in a muffle furnace and calcining at 700-750° C. for 2 hours to obtain an activated mixture; d. Preparation of pure slurry: mixing the activated mixture in step c with sodium carbonate solution and water to prepare a pure slurry material; e. Concrete preparation: The slurry material in step d is mixed with coarse aggregate (slag particles with a particle size greater than or equal to 4.75 mm), fine aggregate (medium sand with a particle size of 1.8 mm) and admixture (14% of Class F fly ash and 10% of S105 grade ground granulated blast furnace slag) to obtain a geopolymer concrete slurry of a mixture of heat-activated slag, cement and calcium hydroxide.
[0047] After the heat-activated slag, cement and calcium hydroxide mixture geopolymer concrete is prepared, the heat-activated slag, cement and calcium hydroxide mixture geopolymer concrete slurry is poured into a mold (150mm×150mm×150mm cubic mold, a total of 12 molds are cast), and a vibration table and manual plugging are used to make it dense, and then it is smoothed and covered with plastic film for maintenance for 28 days.
[0048] Performance test: The heat-activated slag, cement and calcium hydroxide mixture geopolymer concrete prepared in Examples 1-3 was tested for setting time of concrete slurry according to the Standard for Test Methods for Performance of Ordinary Concrete Mixtures (GB / T 50080-2016), and the 7d compressive strength and 28d compressive strength of concrete were tested according to the Standard for Test Methods for Mechanical Properties of Ordinary Concrete (GB / T50081-2019). The test results are shown in Table 1.
[0049] Table 1 Performance test results of geopolymer concrete made of thermally activated slag, cement and calcium hydroxide mixture
[0050] As shown in Table 1, the 7d average compressive strength of Examples 1-3 can reach up to 22.3MPa, and the 28d average compressive strength can reach up to 31.9MPa, with excellent mechanical properties. The project waste slag as the main raw material of concrete can meet the national standards and can be used as a substitute for ordinary concrete in most engineering projects, which can significantly reduce the dependence on traditional concrete raw materials (such as sand and stone aggregates). It not only reduces the energy consumption in the process of raw material mining, but also reduces the emission of related greenhouse gases (such as carbon dioxide), thereby effectively alleviating the global greenhouse effect, realizing the reasonable secondary use of industrial waste resources (i.e. slag), promoting the recycling of resources, saving construction costs, and greatly reducing the transportation and processing costs of construction slag, bringing significant economic benefits to enterprises.
[0051] Embodiment 4, this embodiment provides a prefabricated bay window, including a bay window body 1, one side of the bay window body 1 is evenly provided with CFRP connecting ribs 2 fixed to the building structure, and the material of the bay window body 1 is the heat-activated slag, cement and calcium hydroxide mixture geopolymer concrete prepared by the heat-activated slag, cement and calcium hydroxide mixture geopolymer concrete preparation method proposed in Embodiments 1-3. In specific production, the heat-activated slag, cement and calcium hydroxide mixture geopolymer concrete proposed in the present invention is poured into the mold of the prefabricated bay window, and is formed through vibration, screeding and other processes. The prefabricated bay window after forming can be cured at room temperature or carbonization cured. Normal temperature curing means gradually hardening the concrete under natural environment; carbonization curing can accelerate the carbonization reaction of concrete through a special carbonization curing box to improve its strength and durability. In addition, carbonization curing not only helps to reduce carbon emissions and save energy and reduce consumption, but also can achieve resource recycling and reduce waste generation.
[0052] The use of the geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide as the material of the bay window body can not only achieve the compressive strength, durability and fire resistance of traditional concrete. Its manufacturing process makes full use of industrial waste and construction waste, realizing resource recycling and environmental protection. The use of CFRP connecting bars as a connection method between the bay window and the building structure can greatly enhance the reliability and stability of the connection. CFRP material has high strength and corrosion resistance, can effectively resist erosion and damage from the external environment, and ensure that the bay window always remains stable and safe during long-term use. In addition, CFRP material also has good recyclability, meets the requirements of sustainable development, and is convenient for the production and construction of prefabricated components.
[0053] In this embodiment, the use of prefabricated bay windows using geopolymer concrete, a mixture of heat-activated slag, cement and calcium hydroxide, as the main material in the building structure can be simulated and analyzed by the finite element analysis software abaqus. Figure 3 to Figure 4 As shown, Figure 3 Mise analysis of the precast bay window concrete proposed for this example, Figure 4 This is a mise analysis of CFRP reinforcement for prefabricated bay windows. It can be seen from the figure that the overall strength of the prefabricated bay windows made of heat-activated slag, cement and calcium hydroxide mixture geopolymer concrete is equivalent to that of C30 concrete, which can realize the application and promotion of heat-activated slag, cement and calcium hydroxide mixture geopolymer concrete components.
[0054] The above are implementation methods provided in combination with specific contents, and it is not intended that the specific implementation of this application is limited to these descriptions. Any method structure similar to the present application, or a number of technical deductions or replacements based on the concept of the present application, should be considered as the protection scope of this application.
Claims
1. A method for preparing geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide, characterized in that: The following steps are involved: a. Raw material preparation: obtain slag from the project excavation; b. Raw material pretreatment: drying and sieving the slag in step a to obtain dry slag powder and slag particles of suitable particle size; c. Activation: adding ordinary cement and an alkali activator to the slag powder and the slag particles in step b, and calcining them at high temperature to obtain an activated mixture; d. Preparation of pure slurry: mixing the activated mixture in step c with an alkaline solution and water to prepare a pure slurry material; e. Concrete preparation: Mix the slurry material in step d with coarse aggregate, fine aggregate and admixture to obtain slag polymer concrete slurry.
2. The method for preparing geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide according to claim 1, characterized in that: In step b, the drying temperature is 100-110° C., the drying time is 24 hours, and the particle size of the slag particles is less than or equal to 1.5 mm and greater than or equal to 4.75 mm.
3. The method for preparing geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide according to claim 1, characterized in that: In step c, the high temperature condition is 700-750° C., the calcination time is 2 hours, and the particle size of the slag particles is less than or equal to 1.5 mm.
4. The method for preparing geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide according to claim 1, characterized in that: The alkaline solution in step d is a sodium carbonate solution prepared by dissolving sodium carbonate and water in advance, and the amount of the alkaline solution added is controlled between 7% and 9% by weight of the total amount of the liquid activator and the solid raw materials.
5. The method for preparing geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide according to claim 1, characterized in that: In the mixing process of step e, the water-to-solid ratio is 25% to 32%.
6. The method for preparing geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide according to claim 1, characterized in that: In step e, the weight mix ratio of the slag polymer concrete is activated mixture: sodium carbonate: fine aggregate: coarse aggregate: water = 1: 0.2~0.4: 1.5~1.7: 1.2~1.4: 0.1~0.2, the coarse aggregate is the slag particles with a particle size greater than or equal to 4.75 mm, and the fine aggregate is medium sand with a particle size of 1.0 mm~2.0 mm.
7. The method for preparing geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide according to claim 1, characterized in that: The alkaline activator in step c is calcium hydroxide.
8. The method for preparing geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide according to claim 1, characterized in that: The admixtures include S105 grade ground granulated blast furnace slag and Class F fly ash. The particle size of the Class F fly ash is less than 45μm, its specific surface area is 400m² / kg~450m² / kg, and the admixture range is 12~15%; the particle size of the S105 grade ground granulated blast furnace slag is less than 45μm, its specific surface area is 500m² / kg~520m² / kg, and the admixture range is 10~13%.
9. A prefabricated bay window, characterized in that: The invention comprises a bay window body (1), one side of the bay window body (1) is evenly provided with CFRP connecting ribs (2) fixed to the building structure, and the material of the bay window body (1) is a geopolymer concrete of a mixture of heat-activated slag, cement and calcium hydroxide prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Treatment method for construction residue soil in construction waste
CN109956686A
Method for preparing alkali-activated cementing material from engineering muck and alkali-activated cementing material
CN111454011A
Method for preparing volcanic ash active material from building residue soil
CN112979188A